A soil water and solute learning system for small-scale irrigators in Africa - Stirzaker, Richard; Mbakwe, Ikenna; Mziray, Nuru Ressa (Informa UK Limited, 2017)
Better yields of high-value crops are necessary for a profitable irrigation industry in sub-Saharan Africa. We introduced two simple tools, the Chameleon soil moisture sensor and the FullStop wetting front detector, which represent soil water, nitrate and salt levels in the soil by displaying different colours. These tools form the basis of an experiential learning system for small-scale irrigators. We found that farmers quickly learned from the tools and changed their management within a short time. The cost of implementing a learning system would be a small fraction of that of building or revitalizing irrigation schemes.